Raised Serum Homocysteine Level is Associated with Hypertension (Bangladesh Journal of Medical Biochemistry, 2019)
An elevated serum homocysteine concentration is associated with an increased risk of coronary, cerebral, and peripheral vascular disease. The objective of the study was to evaluate the association of serum homocysteine level with hypertension (HTN). This cross sectional analytical study was conducted at Sir Salimullah Medical College & Mitford Hospital and National Health Care Network Dhaka, Bangladesh over a duration of 21 months from July 2012 to May 2014. Fifty HTN patients were included as study subjects and age and sex matched fifty non-HTN healtlhy controls were included. All the clinical measurements were taken and serum Hcy was measured for all study subjects. In this study, females were predominant in both groups, mean age of the HTN patients was 41.0±5.6 years and non-HTN healthy subjects was 38.2±5.2 years. BMI and FBG were found higher in HTN group than that of non-HTN group but the differences were not statistically significant. Systolic and diastolic BP were found significantly higher in HTN group than that of non-HTN group. Serum Hcy level was significantly higher in HTN group (19.93±4.12 μmol/L) than that of non-HTN group (13.20±1.88 μmol/L). This study depicted that serum Hcy had significant correlation with SBP and DBP in HTN. In conclusion, it was seen that elevated serum Hcy level is associated with hytpertension.Bangladesh J Med Biochem 2018; 11(1): 22-25